2019
DOI: 10.1186/s12874-019-0859-9
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of web surveys for obtaining patient-reported outcomes from cancer survivors: a randomized experiment comparing survey modes and brochure enclosures

Abstract: BackgroundCentral cancer registries are often used to survey population-based samples of cancer survivors. These surveys are typically administered via paper or telephone. In most populations, web surveys obtain much lower response rates than paper surveys. This study assessed the feasibility of web surveys for collecting patient-reported outcomes via a central cancer registry.MethodsPotential participants were sampled from Utah Cancer Registry records. Sample members were randomly assigned to receive a web or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…For those registries offering both a Web-based option and a paper option of the survey, most participants completed the paper version which may reflect that the initial contact was via a mailed (paper) letter, since SEER registries do not routinely collect e-mail addresses for contact. In Utah, where potential participants were randomized to receive either the paper survey or Web-based survey only, there was a nonstatistically significant higher response rate for the paper versus Web-based survey (6).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…For those registries offering both a Web-based option and a paper option of the survey, most participants completed the paper version which may reflect that the initial contact was via a mailed (paper) letter, since SEER registries do not routinely collect e-mail addresses for contact. In Utah, where potential participants were randomized to receive either the paper survey or Web-based survey only, there was a nonstatistically significant higher response rate for the paper versus Web-based survey (6).…”
Section: Resultsmentioning
confidence: 95%
“…Five registries exceeded their overall sample size target; Louisiana achieved 98% of their overall sample size goal. Among the 992 total participants, the majority completed paper surveys at five of the registries; in Utah, the randomized trial conducted within the study showed that offering a paper survey only yielded a nonstatistically significant higher response rate than offering the Web survey only (6). At Detroit, the majority of participants (66.9%) completed the survey via a phone interview with a registry staff member.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 Younger persons may be more comfortable with smartphonebased surveys and more likely to respond to surveys, generally. 35,36 Using v-safe data, we were able to assess the effects of mRNA vaccination on daily life activities for the first time in adults. Effects on daily activities were most frequently reported on day 1 after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence that e-mail results in lower response rates, e-mail is significantly less costly to test. Further, there is a need to test if the farmer respondents to e-mail differ than the respondents to postal mail-in the context of medical research they do not differ (Fowler et al 2019;Millar et al 2019). 2.…”
Section: Experimental Contextmentioning
confidence: 99%